1999
DOI: 10.1038/15472
|View full text |Cite
|
Sign up to set email alerts
|

Spastin, a new AAA protein, is altered in the most frequent form of autosomal dominant spastic paraplegia

Abstract: Autosomal dominant hereditary spastic paraplegia (AD-HSP) is a genetically heterogeneous neurodegenerative disorder characterized by progressive spasticity of the lower limbs. Among the four loci causing AD-HSP identified so far, the SPG4 locus at chromosome 2p2-1p22 has been shown to account for 40-50% of all AD-HSP families. Using a positional cloning strategy based on obtaining sequence of the entire SPG4 interval, we identified a candidate gene encoding a new member of the AAA protein family, which we name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
491
1
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 572 publications
(516 citation statements)
references
References 47 publications
(49 reference statements)
7
491
1
9
Order By: Relevance
“…A novel point mutation detected (1633G>T) leads to a missense change in the AAA cassette, substituting a polar residue (Arginine) with a non-polar (Leucine). This residue is conserved in mouse spastin and several other related proteins [Hazan et al, 1999]. The mutation generates a restriction site for BsrI, and restriction digestion revealed that it was not present in 200 control chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…A novel point mutation detected (1633G>T) leads to a missense change in the AAA cassette, substituting a polar residue (Arginine) with a non-polar (Leucine). This residue is conserved in mouse spastin and several other related proteins [Hazan et al, 1999]. The mutation generates a restriction site for BsrI, and restriction digestion revealed that it was not present in 200 control chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…10 The present study reports on the characterization of two distinct Alu insertion-associated deletions in the SPAST gene, alterations of which cause hereditary spastic paraplegia type SPG4 (OMIM 604277). 11 Haplotyping as well as detailed analysis of the sequences involved was used to trace the probable history of the corresponding alleles, and to unravel the likely mutational mechanisms. Our findings enable a better understanding of the formation and evolutionary role of Alu insertion-associated deletions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hazen et al (1999) identified the spastin (SPG4) gene, which encodes a new member of the AAA (ATPase associated with diverse cellular activities) protein family. After this discovery, more than 70 mutations of the SPG4 gene have been reported, including missense, nonsense, and splice-site mutations, as well as insertions and deletions (Bürger et al 2000;de Bantel et al 2001;Fonknechten et al 2000;Hazan et al 1999;Hentati et al 2000;Jiggins et al 2001;Lindsey et al 2000;Namekawa et al 2001;Santorelli et al 2000;Svenson et al 2001). Here, we present a novel missense (I344K) mutation in the SPG4 gene in a large Korean family with pure AD-HSP.…”
Section: Introductionmentioning
confidence: 96%